2003
DOI: 10.1051/lait:2003012
|View full text |Cite
|
Sign up to set email alerts
|

Partition of five aroma compounds between air and skim milk, anhydrous milk fat or full-fat cream

Abstract: -The present study deals with the physicochemical interactions between aroma compounds and various dairy media used as models of complex food matrices, as well as the consequences of the interactions on aroma partitioning between the air and matrix. Five aroma compounds were investigated: amyl and isoamyl acetate, ethyl pentanoate, hexanal and t-2-hexenal. Skim milk, anhydrous milk fat and full-fat cream were chosen as dairy media, while water was used as a reference medium. Apparent partition coefficients of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 23 publications
5
30
0
Order By: Relevance
“…7 shows that this was true for the esters and ketones in this study: at higher fat levels, when relatively less of each compound was in the aqueous phase and more in the fat phase of the feed, the headspace mole fractions were lower. A similar finding was reported by Meynier et al (2003), who measured the volatility of five esters and aldehydes in water, skim milk, anhydrous milk fat and cream. They observed that air/cream partition coefficients were 94-99% lower than the air/water partition coefficients, indicating that the flavour compounds were less volatile in cream than in water.…”
Section: Influence Of Milk Fat On Pervaporation Of Flavour Compoundssupporting
confidence: 87%
See 1 more Smart Citation
“…7 shows that this was true for the esters and ketones in this study: at higher fat levels, when relatively less of each compound was in the aqueous phase and more in the fat phase of the feed, the headspace mole fractions were lower. A similar finding was reported by Meynier et al (2003), who measured the volatility of five esters and aldehydes in water, skim milk, anhydrous milk fat and cream. They observed that air/cream partition coefficients were 94-99% lower than the air/water partition coefficients, indicating that the flavour compounds were less volatile in cream than in water.…”
Section: Influence Of Milk Fat On Pervaporation Of Flavour Compoundssupporting
confidence: 87%
“…Because flavour compound volatilities tend to be much lower in fat than in water (Landy et al, 1996;Meynier et al, 2003), the portion dissolved in the fat phase should not contribute significantly to the driving force. A comparison of Fig.…”
Section: Influence Of Milk Fat On Pervaporation Of Flavour Compoundsmentioning
confidence: 99%
“…The effect of fat melting point was significant in the case of subjects A and C and the effect of mixing speed was significant for subjects A and D. The effect of an increase in fat content, fat melting point and degree of emulsification, when significant, resulted in a reduction of aroma release. The effect of fat as an aroma release suppressor has been demonstrated in both, static and dynamic conditions (Meynier, Garillon, Lethuaut, & Genot, 2003;Weel et al, 2002). Using the lower mixing speed resulted in softer products with less rigid structure that allowed an easier release of aroma compounds.…”
Section: Aroma Releasementioning
confidence: 99%
“…Aroma concentration in the dessert was calculated from the initial accurate weighing. Aroma concentration in the air phase was measured by GC-headspace analyses with acquisition conditions adapted from Meynier, Garillon, Lethuaut, and Genot (2003) where partition coefficients of the four aroma compounds were measured in dairy media. The vials were equilibrated at 50 1C for one hour before analysis and the injected volume was 1500 mL.…”
Section: Determination Of Air-dessert Partition Coefficients Of Aromamentioning
confidence: 99%